Effect of expander extruder processing on nutritive value of maize cobs based complete diet of buffaloes - REDDY, G V N; REDDY, K JOJI (The Indian Journal of Animal Sciences, 2013)
Expander-extruder processed maize cobs (40%) based complete diet, corresponding mash diet and a conventional diet (containing concentrate mixture and ground-maize cobs in 60: 40 ratio as in complete diets i e as such basis) were fed to 3 permanently fistulated male buffaloes using 3 x3 latin square design to assess the effeet ofthese diets on rumen fermentation pattern and nutrient utilization. The DMI and water intake/kg DMI were comparable on all the diets. Total N, TCA-precipitable N and residual N were increased (P<0.01) from conventional diet to mash and expander-extruder processed diet where the trend in NHI-N concentration was reverse. All the N fractions except NH)-N and TVFA concentrations peaked at 4- hr post feeding. The digestibilities of DM, OM and CP were significantly (P<0.05) higher on expanderextruder processed diet compared to other 2 diets. All the animals were on positive N, Ca and P balances under 3 treatments. Expander-extruder processing increased the DCP and TDN contents of diet and the intakes on all the diets were much higher than the recommended level for maintenance of adult buffaloes. The results indicated that the rumen fermentation pattern in buffaloes was normal on maize-cobs based diets and that expander-extruder processing stimulated to some extent the rumen fermentation pattern and enhanced the nutrient utilization of complete diet.